CHILDHOOD IN THE SHADOW OF A LIME AND ORANGE BLOSSOM - Batista, Ozaias Antonio; Gomes, Ana Laudelina Ferreira (Revista Inter-Legere, 2018)
Understanding imagination as an anthropological faculty capable of instigating the being to completely recreate itself, this paper aims to present some experiences lived by Zezé, a protagonist of the novel “O meu pé de laranja-lima” (my lime-orange blossom) in order to problematize the role of the imagination in the constitution of the being, also embracing their sociocultural reality. To accomplish this purpose, we have adopted the phenomenology of Gaston Bachelard's poetic imagination in dialogue with literary images in the “Poetics of reveries” as a theoretical and methodological assumption, since this research is restricted to the novel mentioned. We were able to identify that the images conceived by Zeze enabled another understanding of himself and his reality, due to the creative movement provided by the imaginative. Keywords: My lime and orange blossom. Imagination and poetic. Imagination and poetic images. Oneiric childhood.